Changing Pattern of Livestock Products Trade in India - S Nair, Arya; M, Thirunavukkarasu; A, Serma Saravana Pandian; G, Senthilkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Data on Indian import and export of livestock products from 2010-11 to 2016-17 werecollected from the reports of FAO and APEDA and used for forecasting the future directionof international trade using Markov Chain analysis. The transition probability matrixindicated that India could not retain its previous export of dairy products to Afghanistan andOman. India’s previous export of dairy products to the UAE market was retained at 23.70%.The remaining 58.70% was diverted to other countries. The probability of retention of thepresent quantity of dairy products imported was the highest for other countries (96.40%),followed by import from Denmark (44.20%). India could not retain its previous import ofdairy products from France, Turkey and Italy during the period. The probability of retentionof the present quantity of processed meat export was the highest for UAE (39.70%), followedby other countries (36.9%). India could not retain its previous export of processed meat toQatar and Maldives. There was 100% probability of shifting of export to India from SriLanka to other countries, and from Spain to Sri Lanka. There were 93.50% and 69.70%probabilities to shift India’s import from Belgium to Sri Lanka and from Thailand to SriLanka, respectively. India’s previous buffalo meat export to Iraq market was retained at59.60%. The remaining 40.40% was diverted to other countries (33.70%) and Indonesia(6.60%). Malaysia showed only 7.90% probability to retain its export market from Indiaand its remaining 92.00% share was found directed to Vietnam. India was having 100%probability to retain the import of buffalo meat from Belgium, followed by New Zealand(70.50%) and Australia (26.80%). The probability of retention of export of poultry productsto the Maldives was at 65.10%. India could not retain its previous export of poultry productsto Japan and Vietnam. Vietnam’s share of poultry products imports from India was divertedto other countries (86.10%). India’s previous poultry products import from France marketwas retained at 52.00% and 48% was diverted to others (39.30%).